Primary pure squamous cell carcinoma of breast in a young female - a rare occurrence - Raje, P; Bhandari, S; Gujrati, R (Journal of Pathology of Nepal, 2014)
Primary squamous cell carcinoma of breast is a rare disease. Incidence for primary SCC breast is 0.04-0.1 % of all malignancies of breast. A pure form of primary SCC breast is also described and its incidence is still less. Biologically it behaves differently and usually doesn’t metastasize to lymph nodes, though distant metastasis is more common. They occur usually in elderly women. Mean age of presentation is 54 years. We report the youngest patient so far - a 27 years old woman diagnosed initially as having fibrocystic disease and later as primary pure SCC breast. She did not have any other focus of malignancy in the body and is doing well 3-1/2 years post surgery and radiotherapy. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10322 Journal of Pathology of Nepal (2014) Vol. 4, 600-602